Long-term cardiac prognosis and risk stratification in 260 adults presenting with mitochondrial diseases. (29th July 2015) - Wahbi, Karim; Bougouin, Wulfran; Béhin, Anthony; Stojkovic, Tanya; Bécane, Henri Marc; Jardel, Claude; Berber, Nawal; Mochel, Fanny; Lombès, Anne; Eymard, Bruno; Duboc, Denis; Laforêt, Pascal
Abstract: Aims: The aim of this study is to assess the long-term cardiac prognosis of adults with mitochondrial diseases. Methods and results: Between January 2000 and May 2014, we retrospectively included in this study 260 consecutive patients (60% women) ≥18 years (interquartile range 31–54), with genetically proven mitochondrial diseases, including 109 with mitochondrial DNA (mtDNA) single large-scale deletions, 64 with the m.3243A>G mutation in MT-TL1, 51 with other mtDNA point mutations, and 36 patients with nuclear gene mutations. Cardiac involvement was present at baseline in 81 patients (30%). Single and multiple variable analyses were performed in search of predictors of major adverse cardiac events (MACEs), and hazard ratios (HRs) and 95% confidence intervals (CI) were calculated. Over a median follow-up of 7 years (3.6–11.7), 27 patients (10%) suffered a MACE, defined as sudden death, death due to heart failure (HF), resuscitated cardiac arrest, third-degree atrioventricular block, sinus node dysfunction, cardiac transplantation, or hospitalization for management of HF. Patients with single large-scale mtDNA deletions or m.3243A>G mutations had the highest incidence of MACE. By multiple variable analysis, intraventricular conduction block (HR = 16.9; 95% CI: 7.2–39.4), diabetes (HR = 7.0; 95% CI: 2.9–16.7), premature ventricular complexes (HR = 3.6; 95% CI: 1.4–9.2), and left ventricular (LV) hypertrophy (HR = 2.5; 95% CI: 1.1–5.8) were independent predictors of MACEs. In patients with zero, one, and two or more risk factors, the incidences of MACE were 1.7, 15 and 42%, respectively. Conclusion: Patients with mitochondrial diseases are at high risk of MACE, independently predicted by intraventricular conduction block, diabetes, ventricular prematurity, and LV hypertrophy.